2011
DOI: 10.1002/art.30448
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of neutrophilic inflammation by H2O2 in antigen‐induced arthritis

Abstract: Objective. Neutrophil accumulation contributes to the pathogenesis of rheumatoid arthritis. This study was undertaken to examine the ability of H 2 O 2 to influence neutrophilic inflammation in a model of antigen-induced arthritis (AIA) in mice.Methods. AIA was induced by administration of antigen into the knee joints of previously immunized mice. Neutrophil accumulation was measured by counting neutrophils in the synovial cavity and assaying myeloperoxidase activity in the tissue surrounding the mouse knee jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 49 publications
3
54
0
1
Order By: Relevance
“…There is growing recognition that oxidants play significant anti-inflammatory roles in inflammation (12,14,49), although the exact mechanisms have not been elucidated. We have previously shown that lyso-PS was the predominant modified PS species identified in activated neutrophils, and although roles for several phospholipases in its production were ruled out, an absolute requirement of an active NADPH oxidase was demonstrated (16,17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is growing recognition that oxidants play significant anti-inflammatory roles in inflammation (12,14,49), although the exact mechanisms have not been elucidated. We have previously shown that lyso-PS was the predominant modified PS species identified in activated neutrophils, and although roles for several phospholipases in its production were ruled out, an absolute requirement of an active NADPH oxidase was demonstrated (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophil-generated oxidants, in addition to microbial killing and inciting inflammation, may also play somewhat paradoxical anti-inflammatory roles (11,12). Indeed, deficient func-tioning of the NADPH oxidase is associated with exaggerated inflammation in human and murine models of chronic granulomatous disease (CGD) (13)(14)(15).…”
mentioning
confidence: 99%
“…Defective leukocyte apoptosis and subsequent removal of apoptotic cells by phagocytes is thought to be important for the initiation and propagation of chronic inflammation. The role of NADPH oxidase-derived H 2 O 2 to induce apoptosis of phagocytes and resolution of inflammation has been reported in a model of antigen-induced arthritis [65] . It is possible to take advantage of this function of H 2 O 2 to regulate pathogenic inflammation in chronic wounds.…”
Section: Hydrogen Peroxide: Implications For Chronic Wound Treatmentmentioning
confidence: 99%
“…The total number of leukocytes was determined by counting in a Neubauer chamber after staining with Turk's solution. Differential counts were obtained from cytospin (Shandon III, Thermo Shandon, Frankfurt, Germany) preparations by evaluating the percentage of each class of leukocyte based on nuclear morphology following staining with May-Grünwald-Giemsa [15].…”
Section: Lps-induced Neutrophil Recruitment To Mouse Kneementioning
confidence: 99%